Direct synthesis of quaternary Cd(Zn, S)Se thin films: Effects of composition. (15th November 2017) - Chavan, G.T.; Pawar, S.T.; Prakshale, V.M.; Pawar, S.M.; Ezugwu, S.; Chaure, N.B.; Kamble, S.S.; Maldar, N.N.; Deshmukh, L.P.
Abstract: In the present communication, the binary CdSe and quaternary Cd1 -x Zn x Se1 -y S y (0 ≤ x = y ≤ 0.35) thin films were synthesized using a chemical bath deposition. Thin film deposition was carried out at the optimized conditions (pH = 10 ± 0.1, deposition temperature = 70 ± 0.1 °C, deposition time = 100 min and substrate rotation speed = 65 ± 2 rpm). X-ray diffraction studies confirmed hexagonal-wurtzite crystal structure with the formation of quaternary Cd(Zn, S)Se phase along with binary CdSe, CdS, ZnS and ZnSe, phases of the as-grown Cd1 -x Zn x Se1 -y S y thin films. Elemental analysis showed presence of Cd 2+, Zn 2+, S 2- and Se 2- in the deposited films. Fourier transform infrared spectroscopy shown the bands at 911.15 cm −1 – 901.62 cm −1 which are assigned to the stretching frequency of Cd–Se bond. Scanning electron microscopy show transformation of the microstructure from globular crystallites to a rhomboid flake like network. The electrical conductivity was typically ≈ 10 −7  Ω − 1 cm −1 . At low temperatures, the conduction was by variable range hopping, and this changed to thermally activated grain boundary dominated conduction for T > 350 K.